The Role of Human Resource Management in Achieving Competitive Advantage - Abdullah Muwafaq Yahya Alshafi; Neşe YILDIZ (Academia Open, 2026)
General Background: Contemporary organizations face intensifying global competition that demands strategic approaches to sustaining market position and achieving organizational excellence. Specific Background: Human resource management has evolved from an operational function into a strategic driver of competitive advantage, encompassing talent acquisition, development, training, compensation, and strategic workforce planning that directly influence organizational performance, innovation capacity, and adaptability. Knowledge Gap: Despite availability of financial and technological resources, many organizations struggle to effectively invest in human capital as a lever for competitiveness, demonstrating limited awareness of strategic human resource planning aligned with long-term organizational goals. Aims: This research examines the strategic role of human resource management in building sustainable competitive advantage by analyzing characteristics, skills, and capabilities required of human resources and evaluating how HR practices impact creativity, quality, flexibility, and operational efficiency. Results: Human resources constitute the most influential source for building competitive capabilities; organizations investing in training and development achieve superior innovation and excellence; rare and distinguished competencies prove difficult to imitate; strategic HR planning directly enhances sustainable performance and organizational capabilities. Novelty: The study provides an integrated theoretical framework demonstrating how human resources transform from operational components into value-generating strategic assets through systematic capability development. Implications: Organizations must adopt comprehensive HR strategies integrating recruitment, qualification, motivation, and strategic planning to enhance operational efficiency, foster innovation, strengthen loyalty, and achieve sustainable competitive differentiation in complex business environments.Keywords : Human Resource Management, Competitive Advantage, Strategic Planning, Organizational Performance, Talent DevelopmentHighlight : Strategic HR planning directly enhances sustainable performance and organizational capabilities beyond traditional resources. Rare, skilled talent proves difficult for competitors to replicate, creating lasting advantages. Training and development programs significantly increase creativity, innovation, and operational process efficiency.